A Synchronous Pancreatic Metastasis from Renal Clear Cell Carcinoma, with Unusual CT Characteristics, Completely Regressed after Therapy with Sunitinib. (3rd March 2014) - Lauro, Salvatore; Onesti, Elisa Concetta; Righini, Riccardo; Carbonetti, Francesco; Cremona, Antonio; Marchetti, Paolo
Abstract : We present a case report of a 75-years-old woman affected by renal clear cell carcinoma with a synchronous pancreatic metastasis and a metachronous lung metastasis. This case has two peculiarities. First the pancreatic metastasis was treated just with medical therapy, that is, Sunitinib, instead of the surgical therapy that is mostly considered. Secondly, the pancreatic lesion showed different characteristics on the computed tomography scan compared to the usual pancreatic metastases from renal clear cell carcinoma. The pancreatic metastasis totally regressed after medical treatment and nowadays, four years after the diagnosis, the patient is disease-free.